ANALISIS KEBIJAKAN PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP UNTUK MEWUJUDKAN SDGS DI KOTA BATU - Salim, Agus; Setyawan, Dody; Lestari, Asih Widi (Publicio: Jurnal Ilmiah Politik, Kebijakan dan Sosial, 2025)
This study analyzes environmental protection and management policies in Batu City in an effort to achieve the Sustainable Development Goals (SDGs). Batu City faces various environmental challenges, such as land conversion, reduced green open spaces, and increasing risks of natural disasters. Using a qualitative approach, this research explores the effectiveness of policy implementation based on Law Number 32 of 2009. The findings indicate that stakeholder coordination, community involvement, and local government capacity are key factors in policy effectiveness. The selection of informants in this study used a purposive sampling technique with a total of four informants. Although various initiatives have been implemented, policy execution still encounters challenges in communication, resources, and bureaucracy. Therefore, strategies to enhance public participation, optimize budget allocation, and strengthen inter-agency synergy are necessary to achieve sustainable environmental management in Batu City. Kata kunci: Bureaucracy, Environmental Protection, Batu City, Public Policy, SDGs.